Vertically Aligned MXene Nanosheet Arrays for High‐Rate Lithium Metal Anodes. Issue 18 (18th March 2022) - Chen, Qian; Wei, Yi; Zhang, Xiaokun; Yang, Zhilin; Wang, Fan; Liu, Wei; Zuo, Jinghan; Gu, Xiaokang; Yao, Yong; Wang, Xingguo; Zhao, Feifei; Yang, Shubin; et al.
Abstract: Lithium (Li) metal is considered as one of the best anode materials due to its high theoretical capacity and low reduction potential. However, its practical application is restricted by uneven Li metal dendrite growth. Herein, vertically aligned Ti3 C2 T x MXene nanosheet arrays synthesized by a facile ice template assisted blade coating method are adopted to regulate Li metal nucleation and guide Li metal deposition. This kind of vertical structure exhibits low tortuosity that can achieve homogeneous and fast Li transport. In addition, the rich F and O groups on the Ti3 C2 T x surface are conducive to the formation of a uniform solid–electrolyte interphase layer, which plays an important role in regulating the nucleation and growth of Li metal. Consequently, the vertically aligned Ti3 C2 T x electrodes achieve high Coulombic efficiencies (98.8%) for more than 450 cycles at a fixed areal capacity of 1.0 mAh cm −2 with a current density of 1.0 mA cm −2 . Moreover, it can maintain stable lithium plating/striping behaviors even at an ultrahigh current density of 5.0 mA cm −2 and high areal capacity of 5.0 mAh cm −2 . Furthermore, full batteries (LiFePO4 as cathode) paired with these vertically aligned Ti3 C2 T x electrodes show superior stability and rate performance than the horizontally aligned Ti3 C2 T x electrodes. Abstract : A facile ice template assisted blade coating method is applied to prepare vertical MXene electrodes. The uniform SEI layer and homogeneous current density distribution enable the dendrite‐free Li plating/stripping behaviors on vertical MXene walls. The vertical MXene electrodes show significantly improved cycling stability and rate capability compared to the horizontal MXene electrodes in both half and full cells.